Diseño y construcción de un prototipo para el control automático de temperatura y humedad relativa en secadores con calentamiento eléctrico - Bardales Vargas, Ever Luis (2024)
The general objective of the present thesis was: being designed for and constructing a prototype for the automatic control of temperature and relative humidity in driers with electric heating; for which, initially came true a designing proposal for the construction of said prototype, we determine in this way that his main components are: a PLC, a control of temperature, a relative humidity control, a cylindrical tunnel, an electrical resistance, a fan and an extractor. Straightaway, became elaborate the logic circuit making use of the software Zelio Soft2 V5.4.2, which allowed determining the quantity of inputs and physical outs that were used in the PLC, which worked out: four inputs (I1, I2, IB and IC) and three physical outs (Q1, Q2 and Q3); in the same ones that got connected the push-button I1, the push-button I2, the contact of the control of temperature, the contact of the control of relative humidity, the electrical resistance, the fan and the extractor, respectively. The results of performance testings suggested the following: a direct relationship between the entrance state is IB with the state of the physical exit Q1 of the PLC, there is a direct relationship between the entrance state IC with the state of the physical exit Q2 of the PLC; finally, an inverse relationship between the entrance state is IC with the state of the physical exit Q3 of the PLC. This way the present thesis was concluded, coming true with the realistic general and simultaneously trying on his general hypothesis.